2012
DOI: 10.3329/bjvm.v9i1.11207
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Production of Necrotic Enteritis in Broiler Chickens

Abstract: The present study was conducted to isolate and identify the Clostridium perfringens, the etiology of necrotic enteritis (NE) from broiler chickens and experimental production of NE with this isolate. A total of 50 samples were collected from jejunum of necropsied birds for isolation and identification of Cl. perfringens. Out of 50 samples, only 4 isolates of Cl. perfringens were isolated and identified (prevalence 8%). In experimental NE, the birds of group A (orally administered with only 0.1 ml (1x10 3 sporu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The histological finding in this study confirmed the diagnosis of each species as showed presence of gametocyte with the characteristic inflammatory cells in duodenal part of intestine. The fact which is agreed with Hein [18] and Asaduzzaman [19].…”
Section: Eimeria Tenella E Acervulina E Maximasupporting
confidence: 77%
“…The histological finding in this study confirmed the diagnosis of each species as showed presence of gametocyte with the characteristic inflammatory cells in duodenal part of intestine. The fact which is agreed with Hein [18] and Asaduzzaman [19].…”
Section: Eimeria Tenella E Acervulina E Maximasupporting
confidence: 77%
“…Indeed, the bacteria live commensally in the gut under normal conditions, but when the gut microecology is drastically altered, these bacteria can proliferate. In acute form, NE causes sudden death of many birds within a few hours, without showing any clinical signs of the disease [2], however, Sub-clinical form may be the most important manifestation of enteritis as it is likely to go undetected and hence untreated [3]. In the global poultry industry, NE is considered an emerging billion-dollar disease [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found be associated with net B positive C. perfringens type A strains [10]. Beta 2 toxin (β 2 ) and its encoding gene cpb 2 had been demonstrated in avian C. perfringens type A strains [11] but its exact role in pathogenesis was needed to be further elucidated. The amino acid sequence of cpb 2 showed no significant homologies with cpb 1 from the beta toxin (15%) or other known proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality due to necrotic enteritis is higher if they are feed on high concentration of wheat, rye, barley and protein (AlSheikhly and Truscott, 1977;Ferdoush et al, 2013). The effect of coccidiosis (Shane et al, 1985;Asaduzzaman et al, 2011) and high protein diet (Ferdoush et al, 2013) in the production of necrotic enteritis have been investigated in Bangladesh. To our knowledge, the effect of high carbohydrate diet in the production of necrotic enteritis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%